Efektivitas Sistem Informasi Berbasis RFID untuk Peningkatan Aksesibilitas Data Koleksi di Perpustakaan Universitas Negeri Padang - Putri, Rahma Diani Ayudian; Marlini, Marlini (Lembaga Yasin AlSys, 2026)
This study aims to describe the effectiveness of a Radio Frequency Identification (RFID)-based information system in improving the accessibility of collection data at Perpustakaan Universitas Negeri Padang. The background of this research lies in the need for an information system that can provide convenience, speed, and efficiency in the retrieval and management of library collections in the digital era. This study employs a quantitative descriptive method. The findings show that the effectiveness of the RFID-based information system at Perpustakaan Universitas Negeri Padang falls into the very good category, with an average score of 3.36 on an interval scale of 3.28–4.03. These results indicate that the RFID system helps enhance service efficiency, facilitates access to collection data, and improves user satisfaction and experience in obtaining information. Thus, the implementation of the RFID-based information system is considered effective in supporting improved accessibility of collection data and the quality of library services.